Genomic analysis of SARS-CoV-2 sequences obtained in Tanzania during the pandemic - Nicholaus P. Mnyambwa; Jinxin Gao; Alex Magesa; Edina Mgimba; Swaminathan Mahesh; Pawan Angra; Juma Kisuse; Clara Lubinza; Lawrence Mapunda; Aman Wilfred; Godfather Kimaro; George P. Judicate; et al. (Journal of Clinical Virology Plus)
Background: Genomic sequences of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from Tanzania remain scarce in GISAID, thus hindering our understanding of how the pandemic evolved in the country. Methods: We performed whole genome sequencing on SARS-CoV-2 samples collected between March 2021 and December 2022 to characterize the virus in Tanzania. Nasal and oropharyngeal swabs were collected from patients seeking health care, incoming travelers as well as from outgoing travelers undergoing pre-travel COVID-19 testing (required for flight boarding). Sample collection, and testing were coordinated by the National Public Health Laboratory. Results: Among 515 samples, 260 (50.49 %) were from outgoing travelers, 227 (44.08 %) Covid-19 suspects seeking care, and 28 (5.44 %) incoming travelers identified at the airport. The majority of the samples came from Dar es Salaam (n = 380, 73.7 %), the country's largest city and the main port of entry. We identified 74 Pango lineages from all the samples, with Omicron 430 (83.50 %) and Delta 79 (15 %) variants being predominant. From the 380 Dar es Salaam samples, 67 Pango lineages were identified, showing both overlapping and unique lineages in each sample type. Conclusion: Our findings reveal a dynamic circulation of SARS-CoV-2 variants over time, with Delta predominantly observed in 2021 and Omicron in 2022 in Tanzania. The temporal prevalence of the identified lineages was consistent with the global epidemiology of the virus. Sustained and expanded genomic surveillance is recommended to track and respond effectively to emerging variants.